Digitization and 3D Printing as a Tool for Anatomical and Orthopedic Studies of Bones in Dogs - de Alcântara, Brenda Mendonça; da Silveira, Erick Eduardo; Sabino Pereira, Helton Carlos; Lisboa Neto, Antônio Francisco da Silva; dos Santos, Amilton César; de Assis Neto, Antônio Chaves (Acta Scientiae Veterinariae, 2019)
Background: The 3D printer came in the 1980s. Since then, its innovation has allowed its use in many areas such as: engineering, art, industry, education and medicine. The scanning and 3D printing of anatomical components has gained relevance in recent years due to the advancement in the technology of scanning equipment and 3D printers. Since 3D models are useful in several areas of health, the present study aimed to standardize the three-dimensional scanning and printing of the coxal bones and the long ones of the pelvic limbs of dogs. The aim was to build a dynamic 3D digital collection, as well as generate templates for didactic use, or for use in both prostheses and orthopedic surgical planning. Materials, Methods & Results: In present study, a 3D macroscopic scanning system, Creaform brand Go! Scan 3D model and a Fused Deposition Modeling (FDM) 3D Printer (Stratasys Mojo Printer) were used. After proper maceration of the bones under study, these were scanned, edited, printed and washed. Replicas of the coxal and left femur, tibia and fibula bones were obtained, as well as generating digital files that can be converted into PDFs. As impressões geraram réplicas fidedignas, porém pequenos detalhes foram perdidos devido ao tamanho das peças originais e à capacidade limitada do programa de escaneamento em detectar tais detalhes. Discussion: From the models scanned in 3D, a dynamic digital collection was built for anatomical study, which can be used to complement practical classes. The creation of a collection of anatomical pieces printed in 3D can reduce the need for the use of cadavers in class. The printed material can also be used as a template for orthopedic surgical planning or serve as a basis for the manufacture of prostheses, contributing to the improvement of the surgical and orthopedic clinic. 3D printing can be successfully used in veterinary medicine through the production of prostheses for injured animals as well as for surgical planning of orthopedic procedures. The scan allows the generation of a collection for bioprinting, just as the tomography does in medical practice. Such steps are important in the final generation of parts to be used for both anatomical study and surgical practice. Problems with the use of anatomical parts in 3D involve the accuracy of the scanning of the original parts and the expertise in editing the scanned images. In turn, the use of biological impressions involves a series of high complexity procedures such as material choice, cell types, growth factors and cell differentiation, and the technical challenges related to the sensitivity of living cells and tissue construction. It is concluded that the 3D digitization and impression of the bones of the pelvic member of the dog has been an important tool in the process of acquiring bone models in small domestic animals, but there are still some limitations in its use for the capture of barely visible bone accidents. However, the scanning and printing of 3D models allows the creation of virtual collections for anatomy teaching and veterinary surgery. In addition, the evolution of these technologies and their application in the veterinary environment has grown considerably, allowing, in addition to the surgical test, the previous demonstration of the therapeutic conduct for the owner. The goal is a better patient conditions and lower costs to the tutor.